Uji kualitas air minum isi ulang disekitar kampus uin Raden Fatah Palembang - Riri Novita Sunarti (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
Humans need water for various purposes, such as bathing, cooking and most importantly for everydayconsumption. Along with today's technological advances and accompanied by increasingly busy human activitythen people tend to choose a more practical way with relatively low cost to meet the needs of drinking water byusing drinking water contents ulang.Permenkes No. 429 in 2010, assessed quality drinking water frommicrobiological parameters are not the discovery of total coliform bacteria in 10 ml of sample. According tosome previous studies, many refill drinking water depot that produce water does not comply with themicrobiological peryaratan. The purpose of this study is to conduct a microbiological water qualitypresentation based on the value of MPN Coliform, by identifying the presence of Escherichia coli in drinkingwater produced depot refill drinking water around the UIN Raden Fatah Palembang. The study was conductedin June 2016 in the Laboratory of the Faculty of Mathematics and Teaching Tarbiyah Raden Fatah StateIslamic University in Palembang. This study uses qualitative descriptive method by comparing the laboratoryresults with standard tables Most Probable Number (MPN), which consists of a test estimation, confirmationtest, and test the amplifier. Get their research results in the bacteria Escherichia coli and Coliform. Of the foursamples unfit for consumption because of a fourth consecutive MPN values per 10 ml coliform bacteria are12.4 per 100 ml; 22.7 per 100 ml; 14 per 100 ml; 1100 per 100 ml, and contains the bacteria Escherichia colisequentially 12.4 per 100 ml; 22.7 per 100 ml; 3 per 100 ml; 1100 per 100 ml.